On Detention and Skill: Reflections on Immigrant Incarceration, Bodying Practices, and the Definition of Skill. (August 2019) - Iskander, Natasha N.
The use of detention as a tool of immigrant enforcement has grown in the United States and around the world. In this article, I examine the practices used to structure the physical detention of immigrants and explore the role that carceral immigrant control plays as a form of labor market governance. I argue that the same security and detention practices that equate being out of status with criminality are also used to tag immigrants as unskilled. Through the delineation of skill categories, which are vested with certain political rights, I posit that this carceral enforcement of skill categories shapes how immigrants are able to navigate the labor market, with particular attention to the implications for recipients of DACA (Deferred Action for Childhood Arrivals) protections.